Pengaruh Lingkungan Kerja dan Disiplin Kerja terhadap Kinerja Karyawan PT ISS Indonesia : Studi pada Divisi Cleaning Service Menara Astra Jakarta - Desi Prasetiyani; Ratna Sari; Jaenudin Jaenudin (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
A conducive work environment and strong discipline are considered key factors in achieving optimal employee performance, particularly in service-based industries. This study examines the influence of work environment and work discipline on employee performance, driven by the need for organizations to enhance productivity and maintain competitive advantage through effective human resource management. This research employs a quantitative approach using a survey method conducted among cleaning service employees of PT ISS Indonesia at Menara Astra, Jakarta. The sample consisted of 60 respondents selected using a census technique. Data were collected through questionnaires based on a Likert scale and processed using SPSS version 29. The analysis technique applied was multiple linear regression to determine both partial and simultaneous effects of the independent variables on employee performance. The results indicate that the work environment and work discipline have a significant effect on employee performance, both individually and collectively. These findings suggest that improvements in workplace conditions and consistent enforcement of discipline can directly enhance employee productivity and effectiveness. Therefore, management should prioritize creating a supportive work environment and implementing clear disciplinary policies to sustain and improve overall performance outcomes.